A Novel Platelet Activating Factor Receptor Antagonist Reduces Cell Infiltration and Expression of Inflammatory Mediators in Mice Exposed to Desiccating Conditions after PRK - Salomon Esquenazi; Jiucheng He; Na Li; Nicolas G. Bazan; Isi Esquenazi; Haydee E. P. Bazan (Clinical and Developmental Immunology)
Purpose. To study the contribution of a novel PAF receptor antagonist LAU-0901 in the modulation of the increased inflammatory response in mice exposed to dessicating conditions (DE) after PRK. Methods. Eighty 13-14 week old female Balb/C mice were used. They were divided into two groups: One group was treated with LAU-0901 topical drops. The other group was treated with vehicle. In each group ten mice served as controls and ten were placed in DE. The other twenty mice underwent bilateral PRK and were divided in two additional groups: ten mice remained under normal conditions (NC) and the other ten were exposed to DE. After 1 week all animals underwent in vivo confocal microscopy, immunostaining and western blotting analysis. Results. Confocal microscopy showed an increased number of reflective structures in the corneal epithelium after PRK and exposure to DE in eyes treated with vehicle as compared to eyes treated with LAU-0901. Significant decrease of COX-2 and Arginase I expression and reduced alpha SMA cells was observed after PRK and exposure to DE in eyes treated with LAU-0901. Discussion: Exposure of mice to a DE after PRK increases the epithelial turnover rate. PAF is involved in the inflammatory cell infiltration and expression of inflammatory cytokines that follow PRK under DE.